ANALYSIS OF THE IMPACT OF THE LEVEL OF POVERTY IN THE SPECIAL AUTONOMY ERA - ACEH: LOOKING AT THE DEGREE OF INDEPENDENCE AND FISCAL DECENTRALIZATION POLICY OF THE REGION - Zikriatul Ulya; Dian Maulana Rizki; Tajul Ula (Jurnal Samudra Ekonomika, 2026)
Poverty in Aceh province is still relatively high, on the other hand the Aceh government has been supported by the existence of special autonomy funds. This study aims to analyze the effect of the degree of independence and fiscal decentralization policies on poverty in 23 regencies/cities in Aceh province for the period 2008-2021. The research model used is a panel data regression model with the Random Effect Model (REM) approach. The results of partial testing show that the degree of independence has a negative and significant effect on poverty and fiscal decentralization policies have a positive and significant effect on poverty. Furthermore, the results of simultaneous testing show that the degree of independence and fiscal decentralization policies have a significant effect on poverty. From the results of this analysis, the Regency/City governments in Aceh province must continue to increase their sources of regional income, especially from regional taxes and regional levies so that they can increase the degree of independence and fiscal decentralization policies which have implications for economic growth and reduce the number of poverty in their regions